Gereja dan Tantangan Radikalisme Agama di Tengah Pluralitas di Indonesia - Johanna Siagian, Riris; Limbong, Sukanto; Marihot Sitanggang, Pintor; Hutahaean, Mona; Hutabarat, Aron (CV. Creative Tugu Pena, 2023)
The Diversity is a real context for the existence of the church in the world. In the Indonesian context, diversity concerns the richness of culture, religion, ethnicity, country, and so on. Indonesia has diversity that must be responded to by all people living in the archipelago, especially because of the richness of ethnic groups and their traditions, customs, cultural riches, and so on. In efforts to respond to diversity, churches in Indonesia really need to develop insight regarding pluralism. This is also an effort to minimize radicalism movements in the name of religion. Within this framework, the church has the responsibility to maintain diversity within the Christian community itself. The solution includes promoting inclusivity in order to build a space for dialogue for all religions and beliefs. Keywords: Challenge of Religious Radicalism, Plurality in Indonesia